Wireless Data Collecting Device of Underground Mining Equipments Based on CC2420 - JIA Yun-hong (Gong-kuang zidonghua, 2011)
In view of problem of inconvenient operation that mining equipments whose position move randomly use single machine collecting mode to collect data, the paper proposed a design scheme of wireless data collecting device based on CC2420. Data collecting module in the device collects data of working state and working parameters of mining equipments by use of PLC in electric cabinet of mining equipments and sends the processed data to wireless transmitter through RS485 serial port; the wireless transmitter sends the data to wireless receiver through radio frequency module CC2420 and the received data are stored in buffer by the wireless receiver, and the data is written in U disk when the buffer is full. The actual application showed that the device can collect data of the mining equipments conveniently.